Makna Lirik Dan Nilai Budaya Pada Lagu Tradisional Jepang Momiji - Rahma Fitri Alifah (Diponegoro University, 2020)
Japan has four distinct seasons each year, called Haru (spring), Natsu (summer), Aki (fall), and Fuyu (winter). Each season has a different natural state, has a different color, and a different atmosphere. For example, in autumn (aki), many leaves turn yellow or red, so this is a characteristic of autumn. This distinctive characteristic is embodied in a song entitled